Improved local control with an aggressive strategy of preoperative (with or without intraoperative) radiation therapy combined with radical surgical resection for retroperitoneal sarcoma. Issue 6 (27th January 2017) - Hull, Melissa A.; Molina, George; Niemierko, Andrzej; Haynes, Alex B.; Jacobson, Alex; Bernstein, Karen De Amorim; Chen, Yen‐Lin; DeLaney, Thomas F.; Mullen, John T.
Abstract : Background and Objectives: We sought to examine our outcomes with advanced preoperative and intraoperative radiation therapy (XRT) combined with aggressive en bloc surgical resection of retroperitoneal sarcoma (RPS) as a strategy to minimize the risk of local recurrence (LR). Methods: From 2003 to 2013, 46 patients with RPS received preoperative XRT followed by radical en bloc surgical resection, with or without intraoperative electron radiation therapy (IOERT). Clinical and pathologic variables predictive of LR and distant recurrence (DR) were evaluated. Results: Thirty‐seven patients had primary tumors and 80% were intermediate grade or higher. All patients received preoperative XRT to a median dose of 50.4 Gy and underwent complete (R0/R1) tumor resection, and 16 patients received IOERT. After a median follow‐up of 53 months, 33 (72%) patients were disease‐free, and there were 8 (17%) DRs, 2 (4%) abdominal recurrences outside of the XRT field, and 5 (10.9%) LRs. High tumor grade and recurrent disease at presentation were the only factors associated with higher rates of recurrence. Conclusions: Excellent local control can be achieved with a coordinated strategy of preoperative (±intraoperative) XRT combined with aggressive en bloc surgical resection of RPS, but systemic failure remains a problem for higher‐grade tumors.